EFEK MEDIASI KEPUASAN PADA PENGARUH KEADILAN KOMPENSASI DAN PENGEMBANGAN SDM TERHADAP KINERJA PEGAWAI - Ali Hamzah; Bambang Subroto; Wuryan Andayani (Universitas Negeri Malang, 2018)
This study aims to improve the ability and efficiency of human resources to employee performance with job satisfaction as a mediation variable. This research was conducted on civil servants within the Directorate General of Budget Ministry of Finance residing in Jakarta. The sampling technique was done by using simple random sampling method and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results of the study show the performance of employees related to equity and human resource development. To improve employee performance that has been established, where to improve the performance of employees can be done by improving equity and human resources development. In addition to direct relationships, the influence of equity and human resource development on employee performance can be done by using job satisfaction as mediation.